Determinants of Digital Economy Development in the EU Member States: The Role of Technological Infrastructure, Human Capital, and Innovation (2017-2022) - Roszko-Wójtowicz, Elżbieta; PLEŚNIARSKA, Aleksandra; Grzelak, Maria M. (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: The rapid digital transformation in the European Union has highlighted the increasing importance of the digital economy in shaping national competitiveness. Recent studies underline the relevance of innovation, human capital, and digital infrastructure as critical factors driving digitalisation. Despite extensive literature on digital economy development, there is a gap in understanding the specific determinants that influence the digitalisation levels across EU member states. This study addresses this gap by examining the relationship between digital infrastructure, human capital, and innovation in fostering digital growth, using the Digital Economy and Society Index (DESI) and European Innovation Scoreboard (EIS) as key indicators. Aim: The aim of this research is to identify and quantify the key determinants influencing the development of the digital economy in the EU member states between 2017 and 2022. Specifically, the study investigates the impact of technological infrastructure, human capital, and intellectual assets on the digital economy. By employing multiple linear regression models, the research aims to clarify how these factors contribute to digital economy growth. Results: The analysis revealed that technological infrastructure and use of IT are consistently the most significant determinants of digital economy development. Human capital, particularly in terms of education and digital skills, gained importance in the later years of the study. Intellectual assets, such as patents and research outputs, also played a critical role, particularly from 2021 onwards. The findings suggest that countries with robust digital infrastructure, well-educated workforces, and strong innovation ecosystems tend to perform better in terms of digitalisation as measured by DESI. These insights provide valuable guidance for policymakers aiming to enhance digital competitiveness through targeted investments in technology, education and innovation.